Arbuscular mycorrhizal fungi and biochar synergistically enhance Cd(II) phytoremediation in Koelreuteria bipinnata - Kang Liu; Hongyan Chen; Naili Zhang; Lijia Dong; Aiping Wu; Xinping Wang; Yanhong Wang (Ecotoxicology and Environmental Safety)
Cadmium (Cd(II)) contamination is a global environmental issue. While synergistic interactions between arbuscular mycorrhizal fungi (AMF) and biochar may enhance Cd(II) phytoremediation in plants, the combined effects on Koelreuteria bipinnata and their underlying mechanisms remain unknown. To address this, we conducted a pot experiment assessing AMF inoculation (sterilized AMF, single or mixed inoculations of Rhizophagus irregularis and Diversispora versiformis) and rice-husk biochar amendment (0 % or 3 % substrate addition) on plant growth, soil properties, and Cd(II) uptake under varying soil Cd(II) concentrations (0, 50 and 150 mg kg−1). The results showed that Cd(II) exposure significantly reduced mycorrhizal colonization and biomass production, while increasing Cd(II) accumulation in soils and plant tissues. Individual AMF or biochar application enhanced plant growth and reduced Cd(II) uptake with distinct advantages: AMF alone excelled in boosting photosynthetic capability, biomass yield, and glomalin-related soil protein (GRSP) secretion; biochar alone more effectively promoted phosphorus absorption and decreased soil Cd(II) bioavailability. Critically, the dual-inoculation of R. irregularis and D. versiformis combined with biochar generated optimal remediation outcomes, achieving a 51 % reduction in shoot Cd(II) uptake, a 76 % decrease in soil total Cd(II) concentration, and a 74 % reduction in diethylenetriaminepentaacetic acid (DTPA)-extractable Cd(II) concentration. These synergistic effects were driven by enhanced spore density and GRSP secretion. Our findings demonstrate that combined R. irregularis-D. versiformis inoculation with biochar amendment provides an effective phytoremediation strategy for Cd(II)-contaminated soils using K. bipinnata.